Loyalty beyond transactions: the role of perceived brand ethics in e-commerce - Peña-García, Nathalie; ter Horst, Enrique (Frontiers in Communication, 2025)
IntroductionAs digital platforms increasingly shape consumer behavior, understanding the factors that drive customer loyalty has become a critical area of research. This study examines the role of Perceived Brand Ethics (PBE), Trust, and Customer Experience (CX) in fostering Brand Engagement (BE) and their subsequent effect on Loyalty within the e-commerce, food delivery, and transportation sectors.MethodsUsing a cross-sectional survey of 1,032 users of Mercado Libre, Rappi, and Uber in Colombia, an emerging economy, data was analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multigroup Analysis (PLS-MGA) to test the proposed hypotheses.ResultsResults confirm that PBE significantly influences Trust and CX, enhancing consumer perceptions and impacting BE through different pathways. While CX strongly predicts BE, Trust does not directly affect engagement. Additionally, BE demonstrates a robust effect on Loyalty, underscoring the importance of emotional connections in digital consumer relationships. Platform-specific differences highlight variations in these relationships across service categories.DiscussionThis study contributes to the literature by integrating ethical perceptions into engagement and loyalty models while offering managerial implications for digital platforms seeking to strengthen customer relationships through ethical transparency, experience optimization, and engagement strategies. These findings provide actionable insights for enhancing and sustaining competitive advantage in digital platforms.